Health related quality of life and psychological wellbeing in patients with hypertrophic cardiomyopathy. - Cox, S. (1997)
OBJECTIVE: To assess the health related quality of life and psychological wellbeing of patients with hypertrophic cardiomyopathy, to correlate these with symptoms, clinical, and psychosocial factors. DESIGN: Questionnaire distributed to 171 hypertrophic cardiomyopathy patients aged at least 14 years, selected at random from a dataset of 480 patients. Assessments included the Short Form 36 (SF-36) Health Survey, the Hospital Anxiety and Depression questionnaire, and measures of adjustment, worry, and patient satisfaction. RESULTS: There was an 80.1% response rate to the questionnaire. Patients had severe limitations in all eight dimensions of quality of life assessed by the SF-36: physical functioning, role limitations owing to physical problems, role limitations owing to emotional problems, social functioning, mental health, general health perceptions, vitality, and bodily pain. Levels of anxiety and depression were also high compared with population norms. Quality of life was particularly impaired in patients with chest pain and dyspnoea, but was less consistently related to clinical cardiological measures. Adjustment to the condition and patient satisfaction were generally good. In multivariate analysis, quality of life was associated with a combination of symptom patterns and psychosocial factors. No differences in quality of life, anxiety or depression were observed between patients with no known family history, those with familial cardiomyopathy, and patients with a family history of premature sudden death. CONCLUSIONS: Hypertrophic cardiomyopathy is associated with substantial restrictions in health related quality of life. Symptoms, adjustment, and quality of interactions with clinical staff contribute to these limitations. Recognition of the problems confronted by patients with hypertrophic cardiomyopathy requires continued efforts at education both of the public and health professionals.